(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article examines the representation of nature as a spiritual guide in William Wordsworth’s seminal works “Tintern Abbey” and “The Prelude.” Wordsworth’s poetry is renowned for embodying the Romantic belief in nature’s power to educate, inspire, and transform the human soul. In “Tintern Abbey,” the poet reflects on the role of nature in fostering tranquility, moral perception, and spiritual renewal, emphasizing personal growth and his evolving relationship with the natural world. In “The Prelude,” nature appears as a constant teacher shaping the poet’s philosophical and creative development. The analysis highlights Wordsworth’s treatment of nature as more than an aesthetic experience, presenting it instead as a means for self-discovery and emotional resilience. The article underscores the significance of Wordsworth’s approach to nature as a central Romantic idea that marks a shift from the constraints of the classical era and the rationalist spirit of the Neoclassical period toward the creative, emotional, and introspective features of Romanticism.